Pengembangan Lembar Kerja Peserta Didik (LKPD) Teks Negosiasi Berbantuan Aplikasi Power Director pada Siswa Kelas X SMA YPIS. Maju Binjai - Dani Prastika (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research is research and development (R&D) which aims to develop negotiation text teaching materials through LKPD assisted by the Power Director Application for Class X YPIS High School students. Maju Binjai which is valid. The development model used is the Borg and Gall model, where in this research the researcher limits development to the development stage. From the stages that have been carried out, the results obtained are that students at YPIS Maju Binjai High School are very interested in using products in learning. "Development of Student Worksheets (LKPD) for Negotiation Texts Assisted by the Power Director Application for Class X YPIS High School Students. Maju Binjai” The research results show that the research results “are included in the “very feasible” category. Presentation of LKPD with material validation score of 83.6%, media 93.3%, teacher assessment 97.5%, student response 86.71%. So the percentage obtained is included in the "very feasible" category, which means "valid" to be used as an LKPD for negotiation texts.